Factors Related to The Incident of Low Birth Weight at Hospital in Palembang - Anggraini, Lia; Podojoyo, Podojoyo; Jasmi, Jasmi; Novita, Nesi (Journal of Maternal and Child Health Sciences (JMCHS), 2025)
Background: Low birth weight refers to a birth weight of less than 2500 grams (<5.5 lbs), irrespective of the gestational age.The risk of low birth weight increases with premature birth (<37 weeks), restricted fetal growth, or both, maternal malnutrition (anemia, etc.), maternal health problems, maternal characteristics (high/low maternal age, parity, poor pregnancy spacing). Research Objectives: to determine the factors associated with the incidence of LBW at Pelabuhan Palembang Hospital. Research method: This type of research is an observational research plan with a cross-sectional approach. The population is all mothers who gave birth and registered in the Pelabuhan Palembang Hospital Medical Records data in 2023, totaling 875 people. A sample of this research are 275 respondents was taken using a systematic random sampling technique. data analysis using the chi square test. The results of the study: The results of the statistical analysis show that there is a relationship between mother’s age (p value=0.001), parity (p value=0.000), gestational age (p value=0.000), anemia status (p value=0.016) with the incidence of LBW and there is no relationship between preeclampsia (p value =0.316) with the incidence of LBW. Conclusion: there is a relationship between age, parity, gestational age, anemia status and the incidence of LBW and there is no relationship between preeclampsia and the incidence of LBW. Background: Low birth weight refers to a birth weight of less than 2500 grams (<5.5 lbs), irrespective of the gestational age.The risk of low birth weight increases with premature birth (<37 weeks), restricted fetal growth, or both, maternal malnutrition (anemia, etc.), maternal health problems, maternal characteristics (high/low maternal age, parity, poor pregnancy spacing). Research Objectives: to determine the factors associated with the incidence of LBW at Pelabuhan Palembang Hospital. Research method: This type of research is an observational research plan with a cross-sectional approach. The population is all mothers who gave birth and registered in the Pelabuhan Palembang Hospital Medical Records data in 2023, totaling 875 people. A sample of this research are 275 respondents was taken using a systematic random sampling technique. data analysis using the chi square test. The results of the study: The results of the statistical analysis show that there is a relationship between mother’s age (p value=0.001), parity (p value=0.000), gestational age (p value=0.000), anemia status (p value=0.016) with the incidence of LBW and there is no relationship between preeclampsia (p value =0.316) with the incidence of LBW. Conclusion: there is a relationship between age, parity, gestational age, anemia status and the incidence of LBW and there is no relationship between preeclampsia and the incidence of LBW.